Integrating UpToDate with case-based learning enhances residents’ clinical decision-making and training satisfaction in critical care training - Zhang, Daowei; Sun, Wenbin; Lu, Xinxing (Frontiers in Medicine, 2026)
ObjectiveCase-based learning (CBL) enhances medical students’ clinical competence but faces limitations like reliance on outdated information and insufficient evidence-based decision-making support. UpToDate, an evidence-based, continuously updated clinical resource, provides current data, standardized pathways, and improved application skills. Integrating UpToDate into CBL offers potential for enhancing the accuracy, timeliness, and multidisciplinary nature of learning. This study developed the “UpToDate-CBL” model for critical care education and evaluated its effectiveness in clinical teaching.MethodsSixty standardized residency trainees were randomized to a CBL group (n = 30) or an UpToDate-CBL group (n = 30). The effectiveness of the UpToDate-CBL model in comparison with CBL model by objectively measuring the students’ theoretical knowledge and clinical skills. Additionally, the quality of teaching was evaluated subjectively through anonymous questionnaires completed by the students.ResultsNo significant differences existed in theoretical knowledge (86.67 ± 5.02 vs. 84.53 ± 3.79, p = 0.097) or clinical skills scores (84.40 ± 4.83 vs. 83.47 ± 4.52, p = 0.442) between groups. However, the UpToDate-CBL group showed significantly higher scores in clinical decision-making (43.47 ± 3.67 vs. 41.20 ± 2.55, p = 0.011) and clinical parameter interpretation (44.87 ± 3.95 vs. 42.27 ± 3.78, p = 0.012). Moreover, self-assessment scores in the UpToDate-CBL group for learning interest (3.83 ± 0.65 vs. 3.20 ± 0.71, p = 0.001), self-learning ability (3.27 ± 0.74 vs. 2.83 ± 0.75, p = 0.034), problem-solving ability (3.50 ± 0.86 vs. 2.87 ± 0.73, p = 0.004), and practical ability (3.57 ± 0.82 vs. 2.93 ± 0.69, p = 0.003) were all significantly higher than in the CBL group. Teaching satisfaction was also significantly higher in the UpToDate-CBL group (90.00% vs. 70.0%, p < 0.05).ConclusionCompared with the CBL model, the UpToDate-CBL approach significantly enhances students’ proficiency in interpreting clinical parameters and clinical decision making, while also effectively fostering their motivation for self-directed learning. This approach demonstrates distinct advantages in clinical reasoning training within the context of critical care medicine; nevertheless, it cannot achieve breakthroughs in teaching basic knowledge and clinical skills.